Role of Device Features towards Purchase Intention Using Mobile Commerce - Shamsudin, Mohd Farid; Shabi, Khairul Shahida; Masrek, Mohamad Noorman; Hussain, Hafezali Iqbal; Salem, Milad Abdelnabi; Yazid, Mohd Faizun Mohamad (International Journal of Engineering and Technology, 2018)
This paper presents the role of device features to adopt mobile commerce (m- commerce) with an extended technology acceptance model (TAM) that integrates few other variables.Â  The proposed model has been empirically tested using data collected from a survey of selected sample of respondents. The survey consists of questionnaire responded by 233 students with 97% response rate among students in located in, Malaysia. Data were analyzed by employing descriptive analysis, correlation and multiple regression analysis, besides other common analysis technique.Â  Findings indicated that device features are positively associated with user intention to adopt m- commerce. The finding contributed in terms of allowing us to understand the determinants that influence the adoption of mobile commerce.